More than just adding water - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A method of growing fruit and vegetables that needs little land, uses two-thirds less water, and increases productivity seven times. Too good to be true? Not quite, but it asks more of you.At a demonstration plot at the Manicaland Agricultural Show...